TEACHER LEARNABILITY PREPAREDNESS IN GOA & STATE INTERVENTION - Amballoor, Renji George; Naik, Shankar B. (International Journal of Psychosocial Rehabilitation, 2020)
The objective of the paper is to understand the dynamics of the ecosystem in influencing theTeacher Learnability Ecosystem in Higher Education institutions in the Indian State of Goa. This study identifies the factors influencing Teacher Learnability and has ranked them on the basis of their influence. The study has worked out the moderation effect of age, nature of appointment and designation on the TeacherLearnability.